Analisa Pengaruh Adanya Instalasi Pengolahan Air Limbah terhadap Kadar Chrom pada Limbah Batik Pabrik di Kabupaten Pekalongan - Tri Minarsih (Jurnal Farmasi Indonesia, 2009)
Waste water originating from batik production is one potential source of water pollution. This is because of batik production of waste water containing organic compounds are quite high, contain chemical compounds that contain dangerous and pathogenic microorganisms that can cause disease. Waste is a heavy metal chromium Cr (VI), which is one type of hazardous waste, can be derived from batik industry, metal plating (electroplating), and tannery (leather tanning). The concentration of chromium was done in the waste analysis before and after experiencing batik processing and industrial wastewater in a river after passing around pabrik. Penetapan chromium content visible spectrophotometer method using Difenilkarbazida. At the preliminary examination that pH of treated wastewater does not meet the requirements of waste water quality standard is five, and also chromium levels that still exceed the Central Java Provincial Regulation No. 10 Year 2004 water quality standards and batik textile industrial waste that is 10.1181 mg / L and after passing through two kilometers of the river flow is still too high at 7.6277 mg / L.